1999
DOI: 10.1002/(sici)1097-4644(19990601)73:3<312::aid-jcb3>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoyl ascorbate: Selective augmentation of procollagen mRNA expression compared withL-ascorbate in human intestinal smooth muscle cells

Abstract: The effect of 6-O-palmitoyl ascorbate on procollagen mRNA levels, collagen synthesis, and collagen secretion was investigated and compared with the effect of L-ascorbate in human intestinal smooth muscle (HISM) cells in vitro. Collagen synthesis, determined by the incorporation of 3H-proline into pepsin-resistant, salt-precipitated collagen, increased in a concentration-dependent manner in response to palmitoyl ascorbate. There was a twofold increase in collagen synthesis at 2.5 and 5 microM. By contrast, L-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…54 Another in vitro study actually showed that AA-PAL increased procollagen synthesis in smooth muscle cells better than AA. 6,55 These mixed results may be due to varied environmental conditions in each experiment, altering the activity of AA-PAL with different pHs, temperatures, and moisture levels. The inconclusive results indicate that more research is needed to determine whether AA-PAL is beneficial or harmful with topical use.…”
Section: A Scorbyl6 -Palmitatementioning
confidence: 99%
“…54 Another in vitro study actually showed that AA-PAL increased procollagen synthesis in smooth muscle cells better than AA. 6,55 These mixed results may be due to varied environmental conditions in each experiment, altering the activity of AA-PAL with different pHs, temperatures, and moisture levels. The inconclusive results indicate that more research is needed to determine whether AA-PAL is beneficial or harmful with topical use.…”
Section: A Scorbyl6 -Palmitatementioning
confidence: 99%